Quantitative variation in plasma angiotensin-i converting enzyme activity shows allelic heterogeneity in the ABO blood group locus - Terao, C; Bayoumi, N; McKenzie, C; Zelenika, D; Muro, S; Mishima, M; Connell, J; Vickers, M; Mark Lathrop, G; Farrall, M; Matsuda, F; Keavney, B (2013)
Angiotensin-I converting enzyme (ACE) occupies a pivotal role in cardiovascular homeostasis. Major loci for plasma ACE have been identified at ACE on Chromosome 17 and at ABO on Chromosome 9. We sought to characterise the genetic architecture of plasma ACE at finer resolution in two populations. We carried out a GWAS in 1810 individuals of Japanese ethnicity; this identified signals at ACE and ABO that together accounted for nearly half of the population variability of the trait. We conducted measured haplotype analysis at the ABO locus in 1425 members of 248 British families using haplotypes of three SNPs, which together tagged the alleles responsible for the principal blood group antigens A1, A2, B and O. Type O alleles were associated with intermediate plasma ACE activity compared to Type A1 alleles (in whom plasma ACE activity was ̃36% lower) and Type B alleles (in whom plasma ACE activity was ̃36% higher). We demonstrated heterogeneity among A alleles: A2 alleles were associated with plasma ACE activity that was very similar to the O alleles. Variation at ACE accounted for 35% of the trait variance, and variation at ABO accounted for 15%. A further 10% could be ascribed to polygenic effects. © 2013 John Wiley and Sons Ltd.